Indonesian Entrepreneur's Barometer 2004 Successful Entrepreneur ( First Report ) - Arnold, John; Waworuntu, Rossy; Mangkusubroto, Kuntoro; Tjakraatmadja, Jann Hidajat; Dhewanto, Wawan (SBM ITB, 2005)
This year, for the first time, Ernst & Young Indonesia and School of Business and Management (SBM), Bandung Institute of Technology (ITB) conducted Indonesian Entrepreneursâ€™ Barometer survey. This first Indonesian Entrepreneurâ€™s Barometer, surveyed Indonesian entrepreneur to get the views of entrepreneurs who are qualified as outstanding amongst their peers. Survey respondents were selected by Ernst & Young Indonesia panels. The survey covers motivations, future plans and perceptions about Indonesian business environment. The results are presented in four sub-chapters under the following title: â€œ Succesful Entrepreneurs and their Businessâ€, â€œ Funding & Wealth Realizationâ€, â€œ Entrepreneurâ€™s Outlookâ€ and â€œ Business Environmentâ€. This paper covers the first two chapters. In todayâ€™s time based competition, high equipment productivity in a manufacturing line is necessary in ensuring a competitive company. Focused Productive Maintenance emphasizes the importance of achieving profitability through equipment effectiveness. This paper demonstrates the logic of Buffer Management and Focused Productive Maintenance to shape competitive advantage in utilizing resources. Some ideas for future are given.